1978
DOI: 10.1007/bf00283642
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of chromosome 7 detected in three unrelated patients

Abstract: Chromosome studies were carried out on three patients for the following reasons: (1) growth retardation and mental subnormality in a boy; (2) marked developmental delay in a female infant; (3) routine check on a man whose wife had a stillborn with congenital anomalies. An interstitial deletion at 7q11::7q21 was observed in all three cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…The previously reported cases with partial monosomy 7q can be classified into five groups based on cytogenetie findings: (1) An interstitial deletion 7qll~7q21 or q22 in 6 cases (Valentine and Sergovich, 1977;Seabright and Lewis, 1978;Klepde Pater et al, 1979;Crawfurd et al, 1979), (2) An interstitial deletion 7q21~7q31 or q32 in 4 cases (Ayraud et al, 1976;Higginson et al, 1976;Franceschini et al, 1978;Klep-de Pater et al, 1979), (3) A terminal deletion 7q32---~7qter in 10 cases (de Grouchy et al, 1968(de Grouchy et al, , 1974Shokeir et al, 1973;Harris et al, 1977;Kousseff et al, 1977;Biederman and Bowen, 1978;Bernstein et al, 1980), (4) An interstitial deletion 7q32---,7q34 in 3 related cases (Nielsen et al, 1979) (The possibility that the interstitial deletion involved the segment 7q32---~q36 was also suggested by the authors. ), and (5)A terminal deletion 7q35~7qter in 2 cases (Francke, 1978;Turleau et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported cases with partial monosomy 7q can be classified into five groups based on cytogenetie findings: (1) An interstitial deletion 7qll~7q21 or q22 in 6 cases (Valentine and Sergovich, 1977;Seabright and Lewis, 1978;Klepde Pater et al, 1979;Crawfurd et al, 1979), (2) An interstitial deletion 7q21~7q31 or q32 in 4 cases (Ayraud et al, 1976;Higginson et al, 1976;Franceschini et al, 1978;Klep-de Pater et al, 1979), (3) A terminal deletion 7q32---~7qter in 10 cases (de Grouchy et al, 1968(de Grouchy et al, , 1974Shokeir et al, 1973;Harris et al, 1977;Kousseff et al, 1977;Biederman and Bowen, 1978;Bernstein et al, 1980), (4) An interstitial deletion 7q32---,7q34 in 3 related cases (Nielsen et al, 1979) (The possibility that the interstitial deletion involved the segment 7q32---~q36 was also suggested by the authors. ), and (5)A terminal deletion 7q35~7qter in 2 cases (Francke, 1978;Turleau et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 reported cases of interstitial 7q deletions, 6 lack bands 7qll-21 or q22 [Crawfurd et al, 1979;Gibson et al, 1982;Klep-de-Pater et al, 1979;Seabright and Lewis, 1978;Valentine and Sergovich, 19771, 7 are monosomic for regions 7q21 +q31 or q32 [Ayraud et al, 1976;Dennis et al, 1977;Franceschini et al, 1978;Higginson et al, 1978;Johnson et al, 1978;Klep-de-Pater et al, 1979;Serup, 19801, and 4 are missing segment 7q31-+q34 [Nielsen et al, 1979;Stallard and Juberg, 19811.…”
Section: Interstitial Deletionsmentioning
confidence: 98%
“…However, subsequent studies using R-and G-banding [de Grouchy et al, 19741 showed that the defect involved a nonreciprocal translocation from chromosome 6 to 7, effectively making the patient monosomic for the region distal to 7q32. Since that first report, another 32 cases of del (7q) have been described, including 15 terminal deletions [Bass et al, 1973;Bernstein et al, 1980;Biederman and Bowen, 1978;Francke, 1978;Friedrich et al, 1979;Harris et al, 1977;Kodama et al, 1980;Kousseff et al, 1977;Shokeir et al, 1973;Taysi et al, 1982;Turleau et al, 19791 and 17 interstitial deletions [Ayraud et al, 1976;Crawfurd et al, 1979;Dennis et al, 1977;Franceschini et al, 1978;Gibson et al, 1982;Higginson et al, 1976;Johnson et al, 1978;Klep-de-Pater et al, 1979;Nielsen et al, 1979;Seabright and Lewis, 1978;Serup, 1980;Stallard and Juberg, 1981;Valentine and Sergovich, 19771. Three patients with a ring 7 chromosome [Nakano and Miyamoto, 1977;Zackai and Breg, 19731 and one with a 7q terminal deletion associated with trisomy 9p [Turleau et al, 19741 have also been reported but are not included in our review of the dysmorphogenetic effects of del (7q) (Table I) because they are aneusomic for segments of the genome other than 7q and therefore do not represent pure 7q monosomy.…”
Section: Introductionmentioning
confidence: 97%
“…The observation of three cases of ectrodactyly in proximal deletions 7q:7q11.2q22 [Pfeiffer, 1984; present case] and 7qllq21 or 22 [Del Porto et al, 19831 suggests a causal relationship, but more information is needed to confirm this. References Valentine and Sergovich, 1977Ayraud et al, 1976Higginson et al, 1976Dennis et al, 1977Franceschini et al, 1978Klep-de Pater et al, 1979Serup, 1980Abuelo and Padre-Mendoza, Young et al, 1984Martin-Pont et al, 1985Johnson et al, 1978Seabright and Lewis, 1978Klep-de Pater et al, 1979Crawfurd et al, 1979Gibson et al, 1982Del Porto et al, 1983Pfeiffer, 1984Young et al, 1984Fryns et al, 1985Frydman et al, 1986 …”
Section: Discussionmentioning
confidence: 98%